The therapeutic role of plastic and reconstructive surgery in the interdisciplinary treatment of soft-tissue sarcomas in Germany: cross-sectional results of a prospective nationwide observational study (PROSa) - Thomas, Benjamin; Bigdeli, Amir Khosrow; Nolte, Steffen; Gazyakan, Emre; Harhaus-Wähner, Leila; Bischel, Oliver E.; Lehner, Burkhard; Egerer, Gerlinde; Mechtersheimer, Gunhild; Hohenberger, Peter; Horch, Raymund E.; Andreou, Dimosthenis; et al. (Cancers, 2022)
Although the involvement of plastic surgery has been deemed important in the treatment of sarcoma patients to avoid oncological compromises and ameliorate patient outcomes, it is not ubiquitously available. The accessibility of defect reconstruction and its therapeutic impact on sarcoma care is the subject of this analysis. Cross-sectional data from 1309 sarcoma patients were collected electronically at 39 German study centers from 2017 to 2019. A total of 621 patients with surgical treatment for non-visceral soft-tissue sarcomas were included. The associated factors were analyzed exploratively using multifactorial logistic regression to identify independent predictors of successful defect reconstruction, as well Chi-squared and Cochran-Mantel-Haenszel tests to evaluate subgroups, including limb-salvage rates in extremity cases. A total of 76 patients received reconstructive surgery, including 52 local/pedicled versus 24 free flaps. Sarcomas with positive margins upon first resection (OR = 2.3, 95%CI = 1.2-4.4) that were excised at centers with lower degrees of specialization (OR = 2.2, 95%CI = 1.2-4.2) were independently associated with the need for post-oncological defect coverage. In this context, the inhouse availability of plastic surgery (OR = 3.0, 95%CI = 1.6-5.5) was the strongest independent predictor for successful flap-based reconstruction, which in turn was associated with significantly higher limb-salvage rates (OR = 1.4, 95%CI = 1.0-2.1) in cases of extremity sarcomas (n = 366, 59%). In conclusion, consistent referral to specialized interdisciplinary sarcoma centers significantly ameliorates patient outcomes by achieving higher rates of complete resections and offering unrestricted access to plastic surgery. The latter in particular proved indispensable for limb salvage through flap-based defect reconstruction after sarcoma resection. In fact, although there remains a scarcity of readily available reconstructive surgery services within the current sarcoma treatment system in Germany, plastic and reconstructive flap transfer was associated with significantly increased limb-salvage rates in our cohort.
Gesehen am 28.10.2022